2021
DOI: 10.3389/fped.2021.711573
|View full text |Cite
|
Sign up to set email alerts
|

Effects of E-Cigarette Exposure on Prenatal Life and Childhood Respiratory Health: A Review of Current Evidence

Abstract: In the last decade, widespread use of E-cigarettes (EC) has occurred all over the world. Whereas, a large amount of evidence on harm to children from conventional cigarette exposure is available, data on health effects in this population throughout different vulnerability windows are still a matter of concern. Exposure to EC during pregnancy may compromise placental function, resulting in fetal structural abnormalities. Specifically, this may cause physio-pathologic changes in the developing lung, which in tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…Additionally, there is indication that using e-cigarettes can cause both short-and long-term respiratory complications in children and future young people who become nicotine addicts are a serious concern. Pediatric populations are more susceptible to the negative consequences of passive vaping because of the low parental perception of the risks associated with e-cigarettes exposure for children (Mescolo et al, 2021). In our study, 67.5% identified correctly that indoor vaping cause harm to non smokers near (passive smoking) if they are exposed to chemicals and aerosols from vaping.…”
Section: Medical Science L Analysis Articlementioning
confidence: 63%
See 1 more Smart Citation
“…Additionally, there is indication that using e-cigarettes can cause both short-and long-term respiratory complications in children and future young people who become nicotine addicts are a serious concern. Pediatric populations are more susceptible to the negative consequences of passive vaping because of the low parental perception of the risks associated with e-cigarettes exposure for children (Mescolo et al, 2021). In our study, 67.5% identified correctly that indoor vaping cause harm to non smokers near (passive smoking) if they are exposed to chemicals and aerosols from vaping.…”
Section: Medical Science L Analysis Articlementioning
confidence: 63%
“…Besides, 94.3% confirmed that vaping or e-cigarettes is not safer for a pregnant woman and her fetus. Pregnancy related exposure to ecigarettes may impair placental function and cause morphological defects in the fetus (Mescolo et al, 2021). The growing lung may experience physiopathologic changes as a result of this, which could subsequently compromise respiratory health.…”
Section: Medical Science L Analysis Articlementioning
confidence: 99%
“…At present, the effects of using e-cigarettes during pregnancy and early fetal development are largely unknown and few studies have addressed the association between e-cigarettes and neurobehavioral deficits [ 169 ]. Two recent epidemiological studies in humans have associated e-cigarette use with an increased risk for low birthweight and fetal growth restriction [ 173 175 ]. Studies in mice investigating the effects of e-cigarettes on different brain regions have found that e-cigarette exposure during pregnancy can alter the transcriptome of the frontal cortex (13–16 mg/mL nicotine), increase global DNA methylation within the brain (13–16 mg/mL nicotine), and dysregulate gene expression in the hippocampus (13 mg/mL nicotine) [ 176 ].…”
Section: Electronic Cigarettes (E-cigs) and Nicotine Replacement Ther...mentioning
confidence: 99%
“…Unlike a cigarette, e‐cigarettes produce a respirable aerosol without burning tobacco. Although the number of studies on the short‐ and long‐term health effects of e‐cigarettes is very limited, recent studies suggested that exposure to e‐cigarettes is also a significant factor that has been shown to increase the incidence of asthma 55 . In 2019, 33% of the youth with asthma who reported having an asthma attack in the previous year were exposed to SHS to e‐cigarettes 54 …”
Section: Environmental Pollutants As Determinants Of Childhood Asthmamentioning
confidence: 99%
“…Although the number of studies on the shortand long-term health effects of e-cigarettes is very limited, recent studies suggested that exposure to e-cigarettes is also a significant factor that has been shown to increase the incidence of asthma. 55 In 2019, 33% of the youth with asthma who reported having an asthma attack in the previous year were exposed to SHS to e-cigarettes. 54 Overall, the evidence contributes to a growing understanding about the timing of SHS exposure and the development of childhood asthma, showing that knowledge of critical time windows of exposure is important in implementing targeted interventions.…”
Section: Tobacco and E-cigarettes Exposure And Childhood Asthmamentioning
confidence: 99%